Collaborative learning in an artifact ecology: A distributed cognition perception - Vasiliou, Christina (My University, 2015)
This work aims to extend our understanding of how groups of learners collaborate in a learning environment rich in technologies, namely an artifact ecology. For the purpose of this investigation we enriched a postgraduate HCI course with four identical technology rich settings that aimed to support student collaborative activities around a design problem. Following an ethnographic approach, we collected qualitative data from an HCI course over three years resulting in a rich dataset for analysis. Initial studies helped us understand the domain knowledge, context, and learners' needs and experiences. Then, using Distributed Cognition (DC) framework we worked toward understanding the interdependencies of learners, tasks, and technologies in the environment and highlighting aspects of redesign. The findings of these individual studies were then combined in order to provide a holistic understanding of the collaborative activities in an artifact ecology.
Keywords: Artifact ecology; Collaborative learning; Distributed cognition; HCI education